2015
DOI: 10.1016/j.rmed.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of asthma and atopy in schoolchildren from Porto Alegre, Brazil, has plateaued

Abstract: In the last decade the prevalence of atopy and lifetime asthma has plateaued, while the prevalence of current asthma fell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Other studies, however, have shown that trends in the prevalence of asthma vary across Brazilian capitals, the prevalence of asthma increasing considerably each year in some cities, such as Florianópolis, (16) and remaining stable in others, such as Porto Alegre. (17) Data on the prevalence of common chronic diseases such as asthma and obesity play an important role in guiding health policies and providing the basis for the development of educational interventions and preventive measures. Therefore, the objective of the present study was to estimate the prevalence of respiratory symptoms and asthma, according to BMI, as well as to evaluate factors associated with physician-diagnosed asthma, in individuals ≥ 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies, however, have shown that trends in the prevalence of asthma vary across Brazilian capitals, the prevalence of asthma increasing considerably each year in some cities, such as Florianópolis, (16) and remaining stable in others, such as Porto Alegre. (17) Data on the prevalence of common chronic diseases such as asthma and obesity play an important role in guiding health policies and providing the basis for the development of educational interventions and preventive measures. Therefore, the objective of the present study was to estimate the prevalence of respiratory symptoms and asthma, according to BMI, as well as to evaluate factors associated with physician-diagnosed asthma, in individuals ≥ 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined trends in the prevalence of asthma in Brazil. 15 - 17 In a study conducted in Brazil and examining 2013 Brazilian National Health Survey data for 60,202 adults (in the 18- to 49-year age bracket), the prevalence of physician-diagnosed asthma was found to be 4.4%. 15 In addition, the study examined temporal trends in the prevalence of asthma, which was found to have remained stable in 1998, 2003, and 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of atopy in childhood has increased since the latter part of the 20th century [7, 8]. And there are very different atopy rates that have been reported in different regions [9, 10]. Studies have reported atopy rates that range from 20.5% in Germany [11] to 57.7% in Hong Kong [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported atopy rates that range from 20.5% in Germany [11] to 57.7% in Hong Kong [12]. The wide range of prevalence of atopy may due to the international variability and regional differences [9,10]. Atopy is associated with an aberrant response to allergens through IgE production by antigen-specific Th2 cells and B cells [13].…”
Section: Introductionmentioning
confidence: 99%